2001
DOI: 10.1562/0031-8655(2001)074<0721:teoaae>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of 5-Aminolevulinic Acid Esters on Protoporphyrin IX Production in Human Adenocarcinoma Cell Lines¶

Abstract: Photodynamic diagnosis (PDD) and photodynamic therapy (PDT) using 5-aminolevulinic acid (ALA)-induced protoporphyrin IX (PPIX) is an interesting approach to detect and treat dysplasia and early cancers in the gastrointestinal tract. Because of low lipophilicity resulting in poor penetration across cell membranes, high doses of ALA should be administered in order to reach clinically relevant levels of PPIX. One way of increasing PPIX accumulation is derivatization of ALA into a more lipophilic molecule. In our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…Our data concerning accumulation of PP(Arg)2 after longer periods are consistent with data obtained using other human adenocarcinoma cell lines from different human (colonic) cell lines (Brunner et al 2001). Furthermore, accumulation in colonic cell lines was studied using flow cytometry, which has some limitations.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Our data concerning accumulation of PP(Arg)2 after longer periods are consistent with data obtained using other human adenocarcinoma cell lines from different human (colonic) cell lines (Brunner et al 2001). Furthermore, accumulation in colonic cell lines was studied using flow cytometry, which has some limitations.…”
Section: Resultssupporting
confidence: 87%
“…Based on this result, we can state that accumulation begins during first 3 min and that it originates from the cell membranes. In an earlier report, Brunner et al (2001) showed that PP IX is present within the cells incubated for 5 min. In our experiments, confocal microscopy allowed us to determine the time more precisely.…”
Section: Resultsmentioning
confidence: 87%
“…In dermatology, multicenter randomized controlled studies have demonstrated the high efficacy of topical ALA-PDT for actinic keratosis, Bowen’s disease and superficial basal cell carcinoma (1719). Although certain reports have addressed the efficacy of ALA-PDT in CRC cells (20,21), these were limited to in vitro studies. Therefore, the objective of this study was to investigate the antitumor effect of ALA-PDT using LEDs for the treatment of CRC cells in a xenograft mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…This compound is normally employed in the form of ester prodrugs, which have an improved absorption when administered as creams. 147 Some of these esters include methyl 5-aminolevulinate (MAOP), Metvix ® , and hexyl 5-aminolevulinate (Hexvix ® , Cysview ® ). Protoporphyrin IX thus generated is selectively accumulated in some tumors because of their accelerated metabolism, which includes a faster processing of ALA.…”
Section: Porphyrins As Photosensitizersmentioning
confidence: 99%